Land Use in the Surrounding Area of Lake-type Wetland Protection Areas - Yeon Hui Jang; Jong-Hak Yun (Geo Data)
In this study, we defined the range of surrounding areas that may impact the ecological environments of three lake-type inland wetland protection areas: Upo Wetland, Mungyeong Doline Wetland, and Duung Wetland. We analyzed the land cover types of each surrounding area to determine the proportion of anthropogenic environmental factors affecting the wetland protection area. The analysis revealed that agricultural areas and urbanized/construction areas were identified as the most significant anthropogenic threats among the land cover types. A comparison of these types across the wetlands showed that in Mungyeong Doline Wetland, there was a high proportion of agricultural and urbanized/construction areas in the zone adjacent to the buffer area (A-2). Therefore, it is necessary to manage this area to prevent the influx of external soil and plant/animal resources, and to establish management strategies for waste and emissions resulting from agricultural activities. For Upo Wetland, the overall high proportion of agricultural areas is expected to have a significant impact. In particular, the northeastern zone (B-2), where Saji-po is located, exhibited the highest proportions of both types. Thus, it is recommended that the agricultural areas surrounding Upo Wetland implement measures to prevent pesticide runoff and contamination from soil, as well as manage domestic wastewater generated from residences. Similarly, in Duung Wetland, a high proportion of agricultural and urbanized/construction areas was observed in the zone adjacent to the buffer area (C-2). This area is particularly vulnerable to issues such as ecosystem fragmentation within the wetland and the inflow of external resources, necessitating effective management strategies. The results of this study can serve as foundational resources for the sustainable conservation and management of the wetland protection area and its surrounding area.